2020
DOI: 10.1002/hpm.3021
|View full text |Cite
|
Sign up to set email alerts
|

Association between non‐attendance to outpatient clinics and emergency department consultations, hospitalizations and mortality in a Health Maintenance Organization

Abstract: Background Non‐attendance to scheduled medical appointments in outpatient clinics is a problem that affects patient health and health‐care systems. Objective Evaluate association of non‐attendance to scheduled appointments in outpatient clinics and Emergency Department (ED) visits, hospitalizations and mortality. Methods Retrospective cohort study of outpatients enrolled in 2015 to 2016 in the Hospital Italiano de Buenos Aires HMO with over five scheduled appointments. Individual non‐attendance proportion was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…age, in uenza-like disease -ILD [35][36][37][38][39][40][41][42]); throughput factors (e.g. triage categories, residence experience, absenteeism [43], congresses [44]); and output factors (e.g. hospital's bed occupation and ow of hospitalized patients [8][9][10][11][12]).…”
Section: Potential Predictorsmentioning
confidence: 99%
“…age, in uenza-like disease -ILD [35][36][37][38][39][40][41][42]); throughput factors (e.g. triage categories, residence experience, absenteeism [43], congresses [44]); and output factors (e.g. hospital's bed occupation and ow of hospitalized patients [8][9][10][11][12]).…”
Section: Potential Predictorsmentioning
confidence: 99%
“…A study developed in Argentina (23) highlights that knowing the patients' absences allows intervening in the quality of health by associating the data of the absentees with the demand for care in the Emergency Department, and with the mortality due to the illnesses of the patients included in the high-complexity university hospital integrated with two hospitals and 20 health centers in Buenos Aires, through integrated electronic medical records in these units. Absence to medical specialties consultations was observed, during the period of one year, with more than five appointments scheduled, of patients with an average age of 63 years, 29.9% of whom were male.…”
Section: Reasons For Absencesmentioning
confidence: 99%
“…Outpatient nonattendance is a frequent problem that affects ambulatory medicine. It represents a significant cost to any health care system, reduces provider productivity and efficiency, delays access to care for other patients, disrupts daily work planning, 1 and can negatively influence patients' health outcomes 2 . Few studies evaluate the economic cost of nonattendance, 3–5 and none evaluate said impact in Latin America.…”
Section: Introductionmentioning
confidence: 99%
“…reported that the cost of no‐shows in 10 US clinics was $14.58 million in 2008 3 and the cost of missed general practice appointments in the UK is £150 million per year 6 . Additionally, some studies have evaluated the potential effect of nonattendances, such as an increase in emergency department visits, unplanned hospital admissions, and any‐cause mortality, 2 especially in specific populations, such as people living with chronic diseases 7 like diabetes 8 hypertension, 9 HIV, 10 and tuberculosis 11…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation